Gilberto Freyre, historiador da vida material: os bichos, as cousas e as técnicas - Westphalen, Cecília Maria (Ciência & Trópico, 2023)
A partir de paradigmas propostos por Fernand Braudel, aponta o pioneirismo freyriano – nas obras Casa-grande & senzala, Sobrados e mucambos e Nordeste – ao considerar a cultura material brasileira em seus ensaios da década de 30. Conclui que o autor realizou "modernas aproximações da história social do Brasil" e uma "história da vida material da civilização da cana-de-açúcar". ABSTRACT Gilberto Freyre, Historian of the Material Life: the Animals, the Things, and the Techniques. v. 29, n. 2, p. 493-505, jul./dez. 2001. Grounded on Fernand Braudel’s paradigms, the essay points out Gilberto Freyre’s pioneering approach – in works such as Casa-grande & senzala (The masters and the slaves), Sobrados e mucambos (The mansions and the shanties), and Nordeste (Northeast) – in regarding Brazilian material culture in his essays published in the thirties. The essay contends that Freyre accomplished “modern approaches to the social history of Brazil” as well as a “history of the material life of the sugar cane civilization.” RÉSUMÉ Gilberto Freyre, historien de la vie matérielle: les bêtes, les choses et les techniques. v. 29, n. 2, p. 493-505, jul./dez. 2001. A partir de paradigmes proposés par Fernand Braudel, l’auteur montre l’esprit pionnier de Gilberto Freyre à travers les oeuvres Casa-grande & senzala, Sobrados e mucambos et Nordeste, en considérant la culture matérielle brésilienne dans les essais de Freyre des années 30. Il conclut que l’auteur réalisa “des approximations modernes de l’histoire sociale du Brésil”et une “histoire de la vie matérielle de la civilisaiton de la canne à sucre”.